2013
DOI: 10.4013/nbc.2013.82.02
|View full text |Cite
|
Sign up to set email alerts
|

Mamíferos de médio e grande porte de uma área agricultável em Terezópolis (GO) com notas sobre métodos de amostragem

Abstract: Mamíferos de médio e grande porte de uma área agricultável em Terezópolis (GO) com notas sobre métodos de amostragem Medium-large sized mammals of an agricultural area in Terezópolis (Goiás State) with sampling methods notes Resumo O Cerrado possui uma grande variedade de habitats e ecossistemas, sendo um dos principais desafios para sua conservação demonstrar a importância que a biodiversidade desempenha no funcionamento desses ecossistemas. A diversidade de mamíferos no Brasil atinge números expressivos e é … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
(24 reference statements)
1
13
0
5
Order By: Relevance
“…This significant number is higher than that in other studies in the state, such as Campos and Lage (2010) with three endangered species and Bernardo and Melo (2013) with one endangered species; these results are similar to other studies such as Ribeiro and Melo (2013) and Silva (2012), both with five endangered species. However, this number may be underestimated, as discussed by Chiarello et al (2008), because of the lack of a state list of endangered species.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This significant number is higher than that in other studies in the state, such as Campos and Lage (2010) with three endangered species and Bernardo and Melo (2013) with one endangered species; these results are similar to other studies such as Ribeiro and Melo (2013) and Silva (2012), both with five endangered species. However, this number may be underestimated, as discussed by Chiarello et al (2008), because of the lack of a state list of endangered species.…”
Section: Discussionsupporting
confidence: 86%
“…Footprints and camera trapping were demonstrated to be the most effective methods to detect mammals. Likewise, these methods were effective in Ribeiro and Melo (2013), Prado et al (2008) and Silva (2012). According to Silveira et al (2003), camera trapping is the most appropriate method for mammal inventory in all environmental conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Among the techniques developed for sampling and monitoring mammals, nowadays there is a tendency to apply non-invasive methods that avoid the need for animal handling and avoid directly perturbing them (Long et al, 2008). The use of camera traps, systematic surveys for detection of signs of presence (e.g., footprints, tracks, scats) and direct observations of animals (e.g., Eisenberg & Thorington, 1973;Emmons et al, 1989;Silveira et al, 2003;Srbek-Araújo & Chiarello, 2005;Lyra-Jorge et al, 2008a;Ribeiro & Melo, 2013) are among the most common non-invasive approaches to study mammals, especially for medium-and large-sized species (SrbekAraújo & Chiarello, 2005;Negrão & Valadares-Pádua, 2006;Tobler et al, 2008). Due to their greater usage, many studies have detailed the efficiencies of these approaches, testing different protocols to assess best use practices and field applicability (e.g., Silveira et al, 2003;Ribeiro & Melo, 2013;Srbek-Araújo & Chiarello, 2013).…”
mentioning
confidence: 99%
“…Another study carried out in the Pantanal (Brazil) obtained better results for detecting footprints of medium-to-largesized mammals with sand plots than with an artificial method involving two overlapping plastic sheets (Olifiers et al, 2011), but those authors suggested that the latter approach might be more efficient in the long term as animals became familiarized with the artificial structure in their landscape. Ribeiro & Melo (2013) also recommended sand plots to sample mammals in Central Brazil, describing the method as being cheap and efficient. However, the authors recognized that sand plots are time-consuming, physically demanding and climate-dependent, and do not allow species abundance quantification.…”
mentioning
confidence: 99%